The role of trust mediates in the influence of social media marketing and Electronic Word-of-Mouth on purchase intention - Kristina, Tria; Sugiarto, Catur (Management and Entrepreneurship: Trends of Development, 2020)
Purchase intention is an important factor for PT Reska Multi Usaha in realizing sustainable business continuity. This study aims at analyzing the increase in purchasing intention through social media marketing and electronic word of mouth with trust as a mediating variable. The type of this research is an explanatory study with a quantitative approach. The respondents of this study is all customers of PT Reska Multi Usaha countless, the sample used 100 respondents with the sampling technique using incidental sampling. The method of gathering data is a questionnaire. The data analysis method used is path analysis. The partial results of hypothesis testing found that social media marketing and electronic word of mouth had a positive and significant trust effect. Electronic word of mouth and trust have a positive and significant effect on purchasing intention. Social media marketing has no effect on purchasing intention. The results of the indirect effect prove that social media marketing and electronic word of mouth have a positive and significant effect on purchasing intention through trust.JEL Classification : M 310; M370; M 390